Causes of Morbidity and Mortality among Neonates and Children in Post-Conflict Burundi: A Cross-Sectional Retrospective Study - Imelda K. Moise (MDPI AG, 2018)
The risk of a child dying before age five in Burundi is almost 1.6 times higher than that in the World Health Organization (WHO) African region. However, variations in the all-cause mortality rates across Burundi have not yet been measured directly at subnational levels, age group and by gender. The objective of this study was to describe the main causes of hospitalization and mortality in children during the neonatal period and at ages 1 to 59 months, for boys and girls, and to assess the total annual (2010) burden of under-five morbidity and mortality in hospitals using hospitalization records from 21 district hospitals. We found variation in the gender and regional distribution of the five leading causes of hospitalization and death of children under five. Although the five causes accounted for 89% (468/523) of all neonatal hospitalizations, three causes accounted for 93% (10,851/11,632) of all-cause hospitalizations for children ages 1 to 59 months (malaria, lung disease, and acute diarrhea), malaria accounted for 69% (1086/1566) of all deaths at ages 1 to 59 months. In Burundi, human malarial infections continue to be the main cause of hospitalization and mortality among under-five children.